Regional carbon budgets: Do they matter for climate policy? - Massimo Tavoni; Detlef van Vuuren (Fondazione Eni Enrico Mattei (FEEM), 2015)
Carbon budgets have emerged as a robust metric of warming, but little is known about the usefulness of regional carbon budgets as indicators of policy. This article explores the potential of regional carbon budgets to inform climate policy. Using the large database of scenarios from IPCC AR5 WGIII, we show that regional budgets are important metrics of the long term contribution to climate change and the effort required to mitigate it. However, their value appears to be more limited for informing short term courses of actions, and for predicting the economic consequences of emission reduction policies.
Keywords: Q54; Q40; 330; Carbon Budgets; Climate Policy; IPCC